1993
DOI: 10.1093/jac/32.1.141
|View full text |Cite
|
Sign up to set email alerts
|

An open trial of cefoperazone plus sulbactam for the treatment of fever in cancer patients

Abstract: Cancer patients received cefoperazone plus sulbactam for 673 febrile episodes presumed to be caused by infection. Overall, 415 (76%) of the 545 evaluable episodes responded. There were 213 responses (84%) amongst the 254 fevers of unknown origin and 202 responses (69%) amongst the 291 documented infections. Fifty-one (61%) of the 83 episodes pneumonia and 74 (64%) of the 115 episodes of bacteraemia responded. Only 39 (58%) of the 67 infections caused by Gram-positive bacteria responded compared with 55 (86%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…These infections may result in septic shock and death in the absence of immediate and aggressive treatment. Until recently, the standard of care for febrile neutropenic patients was the prompt intravenous administration of empirical, broad-spectrum, intravenous antibiotics, usually requiring hospital admission [2,3,4,5,13,14,20]. However, recent work has demonstrated that there is a group of cancer patients with febrile neutropenia at low risk of serious complications from their infection [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These infections may result in septic shock and death in the absence of immediate and aggressive treatment. Until recently, the standard of care for febrile neutropenic patients was the prompt intravenous administration of empirical, broad-spectrum, intravenous antibiotics, usually requiring hospital admission [2,3,4,5,13,14,20]. However, recent work has demonstrated that there is a group of cancer patients with febrile neutropenia at low risk of serious complications from their infection [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies regarding imipenem-cilastatin and sulbactam-cefoperazone plus amikacin as initial therapy for febrile neutropenic cancer patients had been reported 6 , 13 16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…One of the concerns about monotherapy with a single bmonia in febrile oncology patients [13,14]. Therefore, we performed a prospective, randomized study comparing the eflactam drug is that extensive use of this type of therapy will contribute to the emergence and spread of b-lactam-resistant, ficacy and safety of sulbactam/cefoperazone with imipenem as monotherapy for febrile granulocytopenic patients.…”
mentioning
confidence: 99%